DEVELOPMENT OF DIGITAL MULTILAYER ECOLOGICAL MODEL FOR PADANG COASTAL WATER (WEST SUMATRA) - A. Hartoko; M. Helmi (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Coastal water ecology represents a significant gain with regard to regional and local economic, fisheries (including marine culture), tourism and other activities.  Measuring their typical spatial distribution pattern, however, has proved challenging since the real coastal water parameters  as a part of a whole ecosystem and their interactions has never been revealed so far. A GPS guided sampling and in-situ measurement for the field data, digital and an image processing analysis were applied to insure that the simulated coastal water-ecology model was displayed with high levels of spatial,  geodetic and real-data accuracy.  The derived techniques could ultimately provide to coastal managers and decision makers with truthful ecologically and cost-effective means to assess the right zone for fisheries and other coastal water activities based on both temporal and spatial changes.